Competition analysis - Mason, B. R.; Formosa, D. A. (World book of swimming: From science to performance, 2012)
Competition race analysis in swimming has evolved significantly over the past two decades. In the early 2000s FINA (swimming's international governing body) passed a resolution to make competition race analysis obligalory in all FINA International competitions. This was potentially a very progressive initiative; however it was not successfully implemented due to a lack of financial support from FINA. The following chapter investigates the history of international competition race analysis in swimming. It describes the function of race analysis and what it attempts to achieve. The chapter provides a description of how race analysis is performed and how race analysis results are presented to the swimmer and coach. Finally, it illustrates what the swimmer will gain from utilizing race analysis, as well as it investigated the possible future directions of competition race analysis in the sport.